Traditional dance learning as an effort to introduce Sundanese culture in PAUD Riyadussholihin - R Dara Sakhila; Muhammad Rafli Fauji; Yuliawan Kasmahidayat (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Dance education in early childhood serves as a medium for shaping positive character during children's developmental stages. At this age, children also undergo cultural transitions, including exposure to Sundanese culture, which carries values, knowledge, and beliefs. This community service aims to introduce traditional dance as a method to promote Sundanese culture among early childhood students. The service was carried out at PAUD Riyadussholihin in Cipongporang, Katapang, with 35 participants aged 4-6 years. The goal was to foster an appreciation for local culture and instill a sense of national pride through dance. The method used in this service is hands-on practice. Students were introduced to traditional Sundanese dances, such as "Manuk Dadali" and "Mojang Priangan". The sessions were conducted once a week, focusing on both the physical and cognitive development of the children. The findings showed that, despite challenges such as maintaining focus and managing the students' energy levels, the children were highly enthusiastic and engaged in learning the dances. This service demonstrates the potential of traditional dance to enhance cultural knowledge, motor skills, and self-confidence in young children. The experience highlights the importance of incorporating cultural education into early childhood curricula.   Abstrak Pembelajaran seni tari pada pendidikan anak usia dini merupakan sarana pendidikan untuk mengembangkan kepribadian positif pada anak saat proses tumbuh kembangnya. Di masa pertumbuhannya, anak juga mengalami transisi budaya, termasuk budaya Sunda sebagai teladan pengetahuan, nilai, dan kepercayaan. Pengabdian masyarakat ini bertujuan untuk mengenalkan tari tradisional sebagai metode untuk mempromosikan budaya Sunda di kalangan anak usia dini. Kegiatan ini dilaksanakan di PAUD Riyadussholihin di Cipongporang, Katapang, dengan 35 peserta didik berusia 4-6 tahun. Tujuan pengabdian ini adalah untuk menumbuhkan rasa cinta terhadap budaya lokal dan menanamkan karakter cinta tanah air melalui tari. Metode yang digunakan dalam pengabdian ini adalah praktik langsung. Anak-anak diperkenalkan dengan tari tradisional Sunda seperti "Manuk Dadali" dan "Mojang Priangan." Kegiatan dilakukan seminggu sekali dengan fokus pada pengembangan fisik dan kognitif anak. Temuan menunjukkan bahwa meskipun ada tantangan seperti kesulitan dalam mempertahankan fokus dan mengelola energi peserta didik, anak-anak sangat antusias dan terlibat dalam pembelajaran tari. Pengabdian ini menunjukkan potensi tari tradisional dalam meningkatkan pengetahuan budaya, keterampilan motorik, dan rasa percaya diri pada anak usia dini. Pengalaman ini juga menyoroti pentingnya memasukkan pendidikan budaya dalam kurikulum PAUD. Kata Kunci: budaya Sunda; pembelajaran; tari tradisional